2009
DOI: 10.1007/s00420-009-0422-9
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase activity, pesticide exposure and health impact in a population exposed to organophosphates

Abstract: The results suggested the association between occupational pesticide exposure and inhibition of cholinesterases. Thus, medical monitoring of cholinesterase inhibition and intervention programs regarding safety practices during field work are important issues aimed at minimizing adverse health effects of pesticide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
44
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 18 publications
10
44
1
4
Order By: Relevance
“…The same findings were also reported in other studies assessing the adverse effects of pesticides in workers. 2,25,26 In our study, a statistically significant association was found between the neurological symptoms reported by workers and exposure to OP and/or CB. On the other hand, although the decrease in cholinesterase activity was significantly associated with exposure to OP and/or CB, no significant association was found between pesticide-related symptoms and cholinesterase inhibition.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The same findings were also reported in other studies assessing the adverse effects of pesticides in workers. 2,25,26 In our study, a statistically significant association was found between the neurological symptoms reported by workers and exposure to OP and/or CB. On the other hand, although the decrease in cholinesterase activity was significantly associated with exposure to OP and/or CB, no significant association was found between pesticide-related symptoms and cholinesterase inhibition.…”
Section: Discussionsupporting
confidence: 57%
“…These results are similar to those of the study of Catano et al 27 showing a lack of significant association between health symptoms and plasma cholinesterase activity in Peruvian farm workers exposed to OP pesticides. On the other hand, Jintana et al 26 found an association between the inhibition of BChE activity and the occurrence of symptoms in the Thai agricultural population, but only during the high-exposure period.…”
Section: Discussionmentioning
confidence: 98%
“…Only a few persons took precautions even though they knew that the use of protective equipment can protect the body from the adverse health effects of pesticides. 9 Farmers were potentially exposed to pesticide and suffering from Parkinson disease later in life. The study found that many farmers spraying pesticide did not follow right direction.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The non-use of PPE indicated significant into higher percentage of acetyl cholinesterase (AChE) activity inhibition than those who used PPE. 9 A predictive study in Majalengka, West Java also found part of protective equipment (the non-use of long sleeve self-protective wear) and bad personal hygiene aspect (proper shower) influenced cholinesterase activity beside spraying records, smoking during spraying, records of training/extension, spraying position against wind, and age. 10 Pesticide exposure effect to cholinesterase enzyme activity using restriction among fertile women in Brebes showed a significant relation between pesticide types, working time, the use of gloves, and hand-washing behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The observed significant decrease of BChE activity was in accordance with findings of other investigators. Jintana et al (16) suggested that measuring cholinesterase activity could be an admirable biomarker for assessing pesticide exposure and health effect in exposed population. Results of his study showed that there were statistically decrease in BChE activity during high exposure period related to low exposure period.…”
Section: Discussionmentioning
confidence: 99%